The Survivors: Syrian Young Adult Refugee Experiences Navigating the Quebec Education System - Maraj, Arianne; Sherab, Domenique; Calderon-Moya, Milagros; Ghosh, Ratna (Refuge: Canada's Journal on Refugees, 2024)
Canada resettled over 74,000 Syrian refugees since 2015. However, education programs lack awareness needed to successfully promote refugee academic integration. Little research focuses on young adult refugees (YARs) aged out of traditional schools due to asylum displacement and disrupted education, left with adult education schools as their only alternative to complete high school. Drawing upon 29 semi-structured interviews with Syrian YARs in Montreal, findings suggest that this subgroup is unintentionally excluded by educational policy-makers. Although YARs are survivors, their drive was found to be insufficient when confronted with systemic barriers that prevent at-risk students from proceeding smoothly through school to reach their highest potential.